The Metabolic Map into the Pathomechanism and Treatment of PGM1-CDG - Radenkovic, Silvia; Bird, Matthew J; Emmerzaal, Tim L; Wong, Sunnie Y; Felgueira, Catarina; Stiers, Kyle M; Sabbagh, Leila; Himmelreich, Nastassja; Poschet, Gernot; Windmolders, Petra; Verheijen, Jan; Witters, Peter; et al. (American journal of human genetics, 2019)
Phosphoglucomutase 1 (PGM1) encodes the metabolic enzyme that interconverts glucose-6-P and glucose-1-P. Mutations in PGM1 cause impairment in glycogen metabolism and glycosylation, the latter manifesting as a congenital disorder of glycosylation (CDG). This unique metabolic defect leads to abnormal N-glycan synthesis in the endoplasmic reticulum (ER) and the Golgi apparatus (GA). On the basis of the decreased galactosylation in glycan chains, galactose was administered to individuals with PGM1-CDG and was shown to markedly reverse most disease-related laboratory abnormalities. The disease and treatment mechanisms, however, have remained largely elusive. Here, we confirm the clinical benefit of galactose supplementation in PGM1-CDG-affected individuals and obtain significant insights into the functional and biochemical regulation of glycosylation. We report here that, by using tracer-based metabolomics, we found that galactose treatment of PGM1-CDG fibroblasts metabolically re-wires their sugar metabolism, and as such replenishes the depleted levels of galactose-1-P, as well as the levels of UDP-glucose and UDP-galactose, the nucleotide sugars that are required for ER- and GA-linked glycosylation, respectively. To this end, we further show that the galactose in UDP-galactose is incorporated into mature, de novo glycans. Our results also allude to the potential of monosaccharide therapy for several other CDG.
Keywords: Phosphoglucomutase; Galactose; Glycosylation; uridindifosfátglukosa; Cohort Studies; fibroblasty; CDG; kultivované buňky; galactose; Humans; vrozené poruchy glykosylace; uridindifosfátgalaktosa; central carbon metabolism; tracer metabolomics; kohortové studie; glycosylation; PGM1-CDG; mitochondria; Cells, Cultured; Uridine Diphosphate Glucose; Congenital Disorders of Glycosylation; glykosylace; fosfoglukomutasa; lidé; Fibroblasts; galaktosa; nucleotide sugars; Uridine Diphosphate Galactose